2015
DOI: 10.1177/0091415015603173
|View full text |Cite
|
Sign up to set email alerts
|

Social Engagement and Health

Abstract: What are the social factors that matter most to the health of elderly Chinese? Are there any gender and age differences? Using a representative sample of elderly Chinese in Shanghai, the most developed city in China with the nation's largest proportion of elderly residents, this study found that economic conditions, chronic health status, living arrangements, social activity participation, and caring for grandchildren are factors that are most important to the health of elderly Chinese. This is true for both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 48 publications
(51 reference statements)
2
11
0
Order By: Relevance
“…In the context of care-giving, the gendered division of labor has continued to persist: In Korea, despite the public provision of long term care services, the traditional gender role division of caregiving responsibilities persists, with most women being care-givers for their aging parents or grandchildren in families (Korean Women's Development Institute, 2012;Choi, 2014;Kim, 2016). Such a pattern was found in China (Zhang et al, 2015(Zhang et al, 2017.…”
Section: Discussionsupporting
confidence: 52%
“…In the context of care-giving, the gendered division of labor has continued to persist: In Korea, despite the public provision of long term care services, the traditional gender role division of caregiving responsibilities persists, with most women being care-givers for their aging parents or grandchildren in families (Korean Women's Development Institute, 2012;Choi, 2014;Kim, 2016). Such a pattern was found in China (Zhang et al, 2015(Zhang et al, 2017.…”
Section: Discussionsupporting
confidence: 52%
“…Elderly Chinese in China greatly value reciprocal relationship with adult children. They tend to offer substantial economic, housework, and caring support to their children and grandchildren ( Zhang, Feng, Liu, & Zhen, 2015 ). In return, they expect to live with and/or receive care from adult children when needed.…”
Section: Discussionmentioning
confidence: 99%
“…Gender differences, in particular, exist in associations of social connection and the facets of well-being (Schwartz, Keyl, Marcum, & Bode, 2009). Zhang, Feng, Liu, and Zhen (2015) found that the beneficial effects of participation in social activities were particularly salient for the self-rated mental well-being of elderly women than men. However, social participation in Zhang et al's study was not contextualized to community life.…”
Section: Gender Differences In Elderly Mental Healthmentioning
confidence: 99%